Electronic cigarettes’ effects on respiratory health - Tonia Magrì; Bruno Iovene; Luca Richeldi (Nutrimentum et Curae)
Electronic cigarettes (ECs) are electronic nicotine delivery systems (ENDS). ECs have been sold as a safer alternative to traditional cigarettes due to the lack of tobacco combustion since 2006. Their use has risen dramatically not only among current smokers willing to quit, but even among never-smokers and adolescents. Anyway, few data are available on the effects of ECs’ use on respiratory health. This article aims to summarize the available evidence on this matter.